Talk by Mr. Mohd Parid Sulaiman - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
On 21st April 2016, Faculty of Industrial Management organized an Industrial Talk at Astaka, UMP Gambang Campus. The invited speaker was Mr. Mohd Parid Sulaiman, Director of Product Technology Development, Intel Technology (M) Sdn. Bhd., Bayan Lepas Free Trade Zone, Penang.